Kriptografi Ringan dengan Menggunakan Algoritma di Internet Of Things (IoT) - Rudhi Wahyudi Febrianto; Zulianto, Arief (Journal of Informatics Management and Information Technology, 2024)
Internet of Things (IoT) allows objects to generate data and exchange data. IoT applications using microcontrollers such as Arduino do not yet have features to maintain the security of the data in them. Additionally, Arduino has limited computing capabilities. Therefore, it is necessary to apply cryptography with algorithms that have low computation on the Arduino to maintain data security. Cryptography needs to be applied to IoT applications using microcontrollers to maintain the security of data transaction processes and maintain the authenticity of the origin of data. The application of cryptography on microcontrollers must also be light and able to run on microcontrollers, especially Arduino microcontrollers. On Arduino, computing capabilities are limited but most existing security computing algorithms have high computation. Therefore, the applied cryptographic protocol must have efficient algorithms and low computational capabilities. Our research goal is to understand whether lightweight cryptographic approaches can be used to foster secure IoT by design. As a first step in our research process, we conducted a systematic literature review on lightweight cryptography to gather knowledge about the use of this technology and to document its current level. We found 5 use cases of lightweight cryptography in the literature. We also found several problems in that the algorithm execution time on the Arduino Uno was twice as long as the algorithm execution time on a PC. Changes in the value of the data length and digital signature pair affected the results of verifying the validity of the digital signature. We document and categorize current uses of lightweight cryptography, and provide several recommendations for future work to address the issues mentioned above